2009
DOI: 10.1073/pnas.0809568106
|View full text |Cite
|
Sign up to set email alerts
|

SDF-1α stimulates JNK3 activity via eNOS-dependent nitrosylation of MKP7 to enhance endothelial migration

Abstract: The chemokine stromal cell-derived factor-1␣ (SDF-1␣) is a pivotal player in angiogenesis. It is capable of influencing such cellular processes as tubulogenesis and endothelial cell migration, yet very little is known about the actual signaling events that mediate SDF-1␣-induced endothelial cell function. In this report, we describe the identification of an intricate SDF-1␣-induced signaling cascade that involves endothelial nitric oxide synthase (eNOS), JNK3, and MAPK phosphatase 7 (MKP7). We demonstrate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 43 publications
2
58
0
Order By: Relevance
“…Although it has been reported that ADM promotes angiogenesis in vitro through the activation of some signaling pathways (38), the nature of TAM-derived ADM and its mechanism involved in angiogenesis and tumor growth merit further studies. The activation of eNOS in endothelial cells is an important intracellular signaling event for angiogenesis (40)(41)(42). VEGF, similar to ADM, is a proangiogenic factor, which enhances angiogenesis through the activation of eNOS signaling pathway (43).…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been reported that ADM promotes angiogenesis in vitro through the activation of some signaling pathways (38), the nature of TAM-derived ADM and its mechanism involved in angiogenesis and tumor growth merit further studies. The activation of eNOS in endothelial cells is an important intracellular signaling event for angiogenesis (40)(41)(42). VEGF, similar to ADM, is a proangiogenic factor, which enhances angiogenesis through the activation of eNOS signaling pathway (43).…”
Section: Discussionmentioning
confidence: 99%
“…11 This pathway is regulated by eNOS at several levels: CXCR4 signaling is eNOS dependent, and upregulation of matrix metalloproteinase-9 and release of soluble kit ligand are impaired in eNOSknockout mice. 12,13 Interestingly, a single dose of AMD injected under steady-state conditions has been shown to increase circulating levels of SDF-1 and to mobilize hematopoietic progenitors through CXCR4-dependent active secretion of SDF-1 by BM stromal cells.…”
Section: How Can a Short-acting Drug Antagonizing Cxcr4 Develop Sustamentioning
confidence: 99%
“…40,41 Additionally, JNK1 dominant-negative expression suppresses the VEGF-induced proliferation and migration of endothelial cells. 42 JNK3 also promotes endothelial cell migration to facilitate angiogenesis 43 ( Fig. 1).…”
Section: Jnk Isoforms Increase Angiogenesismentioning
confidence: 99%
“…Recently, the influence of JNK3 in the circulatory system, including its importance in angiogenesis, was demonstrated. 43 JNK3 is inactivated by promoter methylation in a variety of cancer cell lines, both immune and epithelial in origin. 111 Its function in the prevention of cytokine-mediated apoptosis in pancreatic β-cells has also been noted recently.…”
Section: Differential Roles For Jnk Isoformsmentioning
confidence: 99%
See 1 more Smart Citation